(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The study reveals the requirements for public procurement procedures on the principles of systematic and consistent, which are enshrined in the Law of Ukraine "On Public Procurement". The signs of systematization and publicity in the general scientific sense and in accordance with the regulated current legislation are determined. The stages and algorithm of the process of systematic and continuous monitoring of public procurement are described. The problem of inconsistency between the Law of Ukraine "On Public Procurement" and the Law of Ukraine "On Public Financial Control in Ukraine" in compliance with the requirements of systematic and consistent monitoring of public procurement procedures at all stages of their implementation by the State Audit Office.